The woman in the window [compact disc, unabridged] : a novel - Finn, A. J. (Harper Audio, 2018)
Anna Fox spends her day drinking wine, watching old movies, and spying on her neighbors. But when she sees something she shouldn't, Anna's world begins to crumble.